3D Liver Tissue Model with Branched Vascular Networks by Multimaterial Bioprinting (Adv. Healthcare Mater. 23/2021). Issue 23 (8th December 2021) - Liu, Xin; Wang, Xinhuan; Zhang, Liming; Sun, Lulu; Wang, Heran; Zhao, Hao; Zhang, Zhengtao; Liu, Wenli; Huang, Yiming; Ji, Shen; Zhang, Jingjinqiu; Li, Kai; et al.
Abstract : 3D Bioprinting In article number 2101405 by Shu Wang, Xiongfei Zheng, Qi Gu, and co‐workers, a bioprinting methodology with multistage‐temperature‐control is developed, producing centimeter‐scale vascularized soft tissues containing branched endothelialized vasculatures and well‐formed 3D capillary networks. It ensures cellular activities and then mimics mature and functional liver tissue.